A systematic review and meta-analysis of effects of early life non-cognitive skills on academic, psychosocial, cognitive and health outcomes. (November 2018) - Smithers, Lisa; Sawyer, Alyssa; Chittleborough, Catherine; Davies, Neil; Davey Smith, George; Lynch, John
Abstract Success in school and the labour market relies on more than high intelligence. Associations between 'non-cognitive' skills in childhood, such as attention, self-regulation and perseverance, and later outcomes have been widely investigated. In a systematic review of this literature, we screened 9, 553 publications, reviewed 554 eligible publications and interpreted results from 222 better-quality publications. Better-quality publications comprised randomized experimental and quasi-experimental intervention studies (EQIs) and observational studies that made reasonable attempts to control confounding. For academic achievement outcomes, there were 26 EQI publications but only 14 were available for meta-analysis, with effects ranging from 0.16 to 0.37 s.d. However, within subdomains, effects were heterogeneous. The 95% prediction interval for literacy was consistent with negative, null and positive effects (−0.13 to 0.79). Similarly, heterogeneous findings were observed for psychosocial, cognitive and language, and health outcomes. Funnel plots of EQIs and observational studies showed asymmetric distributions and potential for small study bias. There is some evidence that non-cognitive skills associate with improved outcomes. However, there is potential for small study and publication bias that may overestimate true effects, and the heterogeneity of effect estimates spanned negative, null and positive effects. The quality of evidence from EQIs underpinning this field is lower than optimal and more than one-third of observational studies made little or no attempt to control confounding. Interventions designed to develop children's non-cognitive skills could potentially improve outcomes. The interdisciplinary researchers interested in these skills should take a more strategic and rigorous approach to determine which interventions are most effective. Smithers et al. find that, although there is some evidence that non-cognitive skills are associated with improved academic, psychosocial and health outcomes, the evidence is weak and heterogeneous. More rigorous research is required in this field.